Catalysed aeration of reduced ilmenite - Ward, Justin M. (Curtin University, 1999)
A study has been conducted on the aeration of reduced ilmenite with emphasis on increasing the aeration speed and understanding the mechanism of the aeration based on laboratory scale experiments. These issues were highlighted by comparing the currently operating Becher process which incorporates the use of an ammonium chloride catalyst in the aeration process.The speed of production of synthetic rutile from the Becher process is currently dictated by the time the reduced ilmenite remains in the aeration tank. As these times can vary greatly for no obvious reason, experiments were conducted to find which parameters could be changed to increase the speed of leaching. It was found that by increasing the oxygen content to 100 per cent the aeration time was reduced by at least half.By replacing ammonium chloride with various other amine compounds as the catalyst it was found there was a relationship between pK[subscript]a and aeration time. It was also found that the more sterically hindered the amine group, the slower the leaching. The use of ethylenediammonium chloride has shown that, when used at two thirds of the ammonium chloride concentration, aeration can be completed an hour (17%) faster than with the ammonium chloride catalyst. Furthermore, when ethylenediammonium chloride was used with a 100 per cent oxygen gas flow the aeration time was reduced by two thirds.Other compounds that did not contain amine groups were also investigated as catalysts in reduced ilmenite aerations. Of those tested only a citric acid / trisodium citrate mixture managed to aerate the reduced ilmenite substantially faster than the standard ammonium chloride catalyst. Other compounds with similar structure to the citrate ion failed to aid the aeration at all.